Answer:
a square backyard with width (x - 9)
Step-by-step explanation:
x²−18x + 81 = x² - (2 x 9) x + 9² = (x - 9)²
width = area / length = (x - 9)² / (x - 9) = x - 9
Length = width
This is a square backyard
A=bh
Where b is the base and h is the height
Answer:
1.) f(x) = x*x - 7x + 10
2.) f(x) = x*x - 5x
3.) f(x) = 4*x*x - 5x - 6
4.) f(x) = 6*x*x -5x + 1
Step-by-step explanation:
1.) 2 and 5 (x -2)(x - 5) = f(x) = x*x - 7x + 10
2.) 0 and 5 f(x) = x*(x -5) = x*x - 5x
3.) -3/4 and 2 (x + 3/4)(x -2) = x*x - (5/4) x - 3/2,
need integers f(x) = 4xx - 5x - 6
4.) 1/2 and 1/3 (x - 1/2)(x - 1/3) = f(x)
x*x - 1/3 x - 1/2 x + 1/6
xx - 5/6 x + 1/6
6 xx - 5x + 1
Answer:
Step-by-step explanation:
rewrite as multiplication
look to factor
, difference of 2 squares and perfect square
, finish factoring and simplify
2(x+3)